IRhom2 regulates CSF1R cell surface expression and non‐steady state myelopoiesis in mice. Issue 12 (28th September 2016) - Qing, Xiaoping; D. Rogers, Lindsay; Mortha, Arthur; Lavin, Yonit; Redecha, Patricia; Issuree, Priya D.; Maretzky, Thorsten; Merad, Miriam; R. McIlwain, David; Mak, Tak W.; Overall, Christopher M.; Blobel, Carl P.; et al.
Abstract : CSF1R was identified as the top shedding substrate of ADAM17 in mEFs by unbiased degradomics screen. Mouse myeloid cells constitutively shed CSF1R through iRhom2/ADAM17 activation. In mixed BM chimera under competitive pressure, iRhom2‐/‐ BM‐derived macrophages showed repopulation advantage over WT cells, possibly due to over‐expression of CSF1R. Abstract : CSF1R (colony stimulating factor 1 receptor) is the main receptor for CSF1 and has crucial roles in regulating myelopoeisis. CSF1R can be proteolytically released from the cell surface by ADAM17 (A disintegrin and metalloprotease 17). Here, we identified CSF1R as a major substrate of ADAM17 in an unbiased degradomics screen. We explored the impact of CSF1R shedding by ADAM17 and its upstream regulator, inactive rhomboid protein 2 (iRhom2, gene name Rhbdf2 ), on homeostatic development of mouse myeloid cells. In iRhom2‐/‐ mice, we found constitutive accumulation of membrane‐bound CSF1R on myeloid cells at steady state, although cell numbers of these populations were not altered. However, in the context of mixed bone marrow (BM) chimera, under competitive pressure, iRhom2‐/‐ BM progenitor‐derived monocytes, tissue macrophages and lung DCs showed a repopulation advantage over those derived from wild‐type (WT) BM progenitors, suggesting enhanced CSF1R signaling in the absence of iRhom2. In vitro experiments indicate that iRhom2‐/‐ Lin − SCA‐1 + c‐Kit + (LSKs) cells, but not granulocyte‐macrophage progenitors (GMPs), had faster growth rates than WT cells in response to CSF1. Our results shed light on an important role of iRhom2/ADAM17 pathway in regulation of CSF1R shedding and repopulation of monocytes, macrophages and DCs.